新加坡华语的现状与前瞻 ：以儿童和成人语言产出、小学华文课本及新闻媒体语言为依据的探讨 = Current trends and future development in Singapore Mandarin : an examination based on the speech production of children and adults, Chinese textbooks used for primary school children, and language use in news media - 胡翠月 Foo, Cui Yet (Nanyang Technological University, 2021)
新加坡华语长年以来受到不同语言，尤其是英语和方言的影响，发展至今已变成了汉语变体之一。新加坡双语政策导致语言接触在其社会当中是一个极为普遍的现象，从而为新加坡华语带来了莫大的影响，引发语用方面的变化且形成一些定型的语用特征。本研究试从新加坡华人的语用追溯新加坡华语特征产生的原因，并通过对比一般大众、学校和官方媒体三方面的语用规范总结出新加坡华语的现状，从而对新加坡华语的未来展望做初步推测。Singapore Mandarin has long been under influence by various languages, especially the English language and Mandarin dialects, and has since developed into a language variety. The bilingual policy in Singapore has caused language contact to be a common phenomenon in the society, thus having a great influence on Singapore Mandarin, and eventually causing the emergence of language use which is unique to the language users in Singapore. This paper attempts to understand the causes of some unique features in Singapore Mandarin through studying the language use of 3 main groups: the general population, educational institutions and media organizations. Through comparing language use across the aforementioned groups, the paper also attempts to summarize current trends in Singapore Mandarin and provide some foreshadowing to future development in Singapore Mandarin.